Cassava trait preferences of men and women farmers in Nigeria: implications for breeding - Teeken, Béla; Olaosebikan, O.; Haleegoah, J.; Oladejo, E.; Madu, Tessy; Bello, A.; Parkes, Elizabeth Y.; Egesi, Chiedozie N.; Kulakow, Peter A.; Kirscht, H.; Tufan, Hale Ann (Springer, 2018)
Nigeria is the world’s largest cassava producer, hosting a diverse array of cassava farmers and processors. Cassava breeding programs prioritize “common denominator” traits in setting breeding agendas, to impact the largest possible number of people through improved varieties. This approach has been successful, but cassava adoption rates are less than expected, with room for improvement by integrating traits in demand by farmers and processors. This paper aims to inform breeding priority setting, by examining trait and varietal preferences of men and women cassava farmer/processors. Men and women in eight communities in Southwest and Southeast Nigeria were consulted using mixed methods. Women and men had significantly different patterns of cassava use in the Southwest. Fifty-five variety names were recorded from the communities demonstrating high genetic diversity maintained by growers, especially in the Southeast. High yield, early maturity, and root size were most important traits across both regions, while traits women and men preferred followed gender roles: women prioritized product quality/cooking traits, while men placed higher priority on agronomic traits. Trait preference patterns differed significantly between the Southeast and Southwest, and showed differentiation based on gender. Patterns of access to stem sources were determined more by region and religion than gender.